DEVELOPMENT OF CIVIC COMPETENCIES OF STUDENTS: NEW APPROACHES AND PRACTICES UNDER NUSH - Iliichuk, Liubomyra; Verezhak, Lilia (Mountain School of Ukrainian Carpaty, 2021)
The article emphasizes that the formation of civic competence of students is one of the key tasks of the New Ukrainian School. The need to form a citizen of Ukraine, for whom a democratic civil society is a center for the disclosure of his abilities and capabilities, the satisfaction of personal and public interests, is emphasized. An analysis of modern approaches to the formation of civic competence of students, in particular through the introduction of education for democratic citizenship (EDC) and human rights education (HRE) in the educational process of GSEI. It is noted that this is a new direction in education, which is the subject of international attention and educational strategies. EDC / HRE is based on competency, activity, personality-oriented approaches that are a priority in creating an educational environment. The peculiarity of education for democratic citizenship and human rights education is that the content, forms and methods of teaching are built in the dimension of «learning about / for / through democracy and human rights», which enriches the role of teacher and student in the learning process. The leading idea of this direction is to encourage children to become active citizens who are able to participate in shaping the future of society through the teaching of democracy and human rights. In Ukraine, the implementation of EDC / HRE is carried out thanks to the Swiss-Ukrainian project «Development of civic competencies in Ukraine» – DOCCU. It is noted that today in European countries and in our country there is experience in developing and implementing training courses on EDC / HRE, which requires dissemination and detailed study by teacherspractitioners, educational experts and scientists. The experience of introducing education for democratic citizenship (EDC) and human rights education (HRE) into the educational process of the New Ukrainian School is generalized.